2006
DOI: 10.1111/j.1464-410x.2006.06207.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravesical instillation of cyclooxygenase‐2 inhibitor on the expression of inducible nitric oxide synthase and nerve growth factor in cyclophosphamide‐induced overactive bladder

Abstract: stained immunohistochemically for iNOS and NGF. RESULTSIn the OAB rats, the contraction interval and intercontraction interval were significantly shorter than in control rats, and the contraction time and pressure were significantly greater. In the COX-2 inhibitortreated rats, the contraction interval and intercontraction interval were significantly longer than in the OAB rats, and the contraction time was significantly shorter. On immunohistochemical staining, there was no iNOS activity and NGF activity was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 18 publications
2
34
0
1
Order By: Relevance
“…Similar histological findings have been observed in humans with persistent bacteriuria and recurrent UTI [26]. In a rodent model of OAB, Jang et al [27] demonstrated that intravesical cyclooxygenase (COX)-2 inhibitors can alter the expression of inflammatory modulators and cytokines in the bladder tissues improving the parameters of detrusor contraction. In mice, Hannan et al [24] found that the inhibition of COX-2 reduced pyuria and prevented mucosal damage, but did not disrupt any known beneficial mucosal responses, such as urothelial exfoliation and overall immune cell recruitment to the bladder.…”
Section: Chronic Inflammation and Nonsteroidal Anti-inflammatory Drugssupporting
confidence: 57%
“…Similar histological findings have been observed in humans with persistent bacteriuria and recurrent UTI [26]. In a rodent model of OAB, Jang et al [27] demonstrated that intravesical cyclooxygenase (COX)-2 inhibitors can alter the expression of inflammatory modulators and cytokines in the bladder tissues improving the parameters of detrusor contraction. In mice, Hannan et al [24] found that the inhibition of COX-2 reduced pyuria and prevented mucosal damage, but did not disrupt any known beneficial mucosal responses, such as urothelial exfoliation and overall immune cell recruitment to the bladder.…”
Section: Chronic Inflammation and Nonsteroidal Anti-inflammatory Drugssupporting
confidence: 57%
“…In the urethra, topical application of PGE 2 causes relaxation of the sphincter (Yokoyama et al, 2007). Likewise, intravesical instillation of an inhibitor of the COX-2 enzyme improved bladder function in an animal model of OAB (Jang et al, 2006). This supports a role for this prostanoid during bladder dysfunction and has justified a few inconclusive clinical trials regarding the use of non-steroidal anti-inflammatory drugs in the treatment of OAB.…”
Section: Prostaglandinsmentioning
confidence: 76%
“…[17][18][19][20][21][22][23] NGF activity would also increase in cyclophosphamide-induced OAB animal bladder mucosa, submucosa and detrusor. 8 Other clinical investigations had proven the effectiveness of HA on OAB and interstitial cystitis. [24][25][26] The effectiveness of HA treatment in OAB animals can be well shown in the NGF profile of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…5 Coating the bladder inner surface with other glycoproteins, such as pentosanpolysulphate 6 and hyaluronic acid (HA), is also believed to help prevent further inflammation in the bladder. 7 The increase of bladder hyperactivity 8 and inflammation 9 in cystitis-OAB was found to be related to nerve growth factor (NGF). Increased amounts of NGF in urine has been found in various kinds of pathophysiological bladder conditions, including overactive bladder 10 and inflammatory cystitis.…”
Section: Introductionmentioning
confidence: 99%